The philosophy scare : the politics of reason in the early Cold War - McCumber, John (Chicago : The University of Chicago Press, 2016)
From the rise of formalist novels that championed the heroism of the individual to the proliferation of abstract art as a counter to socialist realism, the years of the Cold War had a profound impact on American intellectual life. As John McCumber shows in this fascinating account, philosophy, too, was hit hard by the Red Scare. Detailing the immense political pressures that reshaped philosophy departments in midcentury America, he shows just how radically politics can alter the course of intellectual history. McCumber begins with the story of Max Otto, whose appointment to the UCLA Philosophy Department in 1947 was met with widespread protest charging him as an atheist. Drawing on Otto's case, McCumber details the hugely successful conservative efforts that, by 1960, had all but banished the existentialist and pragmatist paradigms not to mention Marxism from philosophy departments all across the country, replacing them with an approach that valorized scientific objectivity and free markets and which downplayed the anti-theistic implications of modern thought. As he shows, while there have since been many instances of definitive and even explosive rejection of this conservative trend, its effects can still be seen at American universities today.
The cudgels of freedom: Cold War philosophy's theory of objects -- Academic stealth in the early Cold War -- Reductionism as the favored form of naturalism -- The carrots of reason: Cold War philosophy's theory of subjects -- The politics of rational choice -- Rational choice philosophy as "scientific philosophy" -- Purifying the academy -- Organizing academic repression: the California plan -- Rationalizing academic repression: the Allen formula -- Epilogue: the two fates of Cold War philosophy.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: University of California, Los Angeles. -- Department of Philosophy -- History -- 20th century; University of California, Los Angeles. -- Department of Philosophy; Philosophy -- Study and teaching -- Political aspects -- California -- History -- 20th century; Academic freedom -- California -- History -- 20th century; Philosophy -- Political aspects -- United States -- History -- 20th century; Cold War; Rational choice theory -- Political aspects -- United States; Naturalism -- Political aspects -- United States; United States -- Intellectual life -- 20th century -- Political aspects; Philosophie -- Étude et enseignement -- Aspect politique -- Californie -- Histoire -- 20e siècle.; Liberté de l'enseignement -- Californie -- Histoire -- 20e siècle.; Philosophie -- Aspect politique -- États-Unis -- Histoire -- 20e siècle.; Guerre froide; Théorie des choix rationnels -- Aspect politique -- États-Unis.; Naturalisme -- Aspect politique -- États-Unis.; États-Unis -- Vie intellectuelle -- 20e siècle -- Aspect politique; PHILOSOPHY -- History & Surveys -- Modern; Academic freedom; Intellectual life -- Political aspects; Philosophy -- Political aspects; Rational choice theory -- Political aspects; California; United States; 1900-1999; Cold War; McCarthyism; UCLA; philosophy; History